PENGUATAN KARAKTER BERNALAR KRITIS DAN KREATIF SISWA DALAM PEMBELAJARAN DIFERENSIASI BERBASIS DEEP LEARNING DI SEKOLAH DASAR - Sari, Vivi Yunita; Supriyadi (STKIP Citra Bakti, 2025)
The implementation of the deep learning curriculum as a national curriculum that emphasizes the strengthening of critical and creative thinking characters in facing the 21st century is becoming increasingly urgent, especially at the elementary education level which is the main foundation in character formation. These challenges require a deep and meaningful learning approach, which is adaptive and transformative. This study aims to describe the strengthening of critical and creative reasoning characters in deep learning-based differentiation learning. This research approach uses qualitative with a case study type. Data collection uses in-depth interview methods, non-participant observation, and documentation. The data analysis used is the interactive analysis of the Miles and Huberman model with three activities, namely data coding, data presentation, and drawing conclusions and testing the validity of the data using triangulation of sources and methods. The results of this study indicate that teachers in implementing deep learning-based differentiated learning in strengthening critical and creative thinking characters adjust the learning process to the different interests, learning styles, and learning readiness of students. Teachers carefully select learning resources that are relevant to students. The group discussion method is applied in deep learning-based differentiated learning to help students process information, exchange ideas and filter information. This study shows that there is a strengthening of students' critical and creative reasoning characters through tasks and activities designed according to individual characteristics, students are not only invited to understand concepts, but also analyze information, evaluate natural and social phenomena, and formulate solutions. Students are motivated to state the reasons for each answer given and explain their thinking process, so that critical reasoning skills can develop optimally.